As estratégias linguístico-discursivas e o modo de organização do discurso funk - Paulon, Andréa (2011)
This research work has the objective to examine the linguistic-discursive strategies and the mode of discourse organization of the funk, which generally presents topics about sexuality, violence, drugs and various social issues. In this sense, these issues are inscribed in the materiality of language by a vocabulary that explores a specific semantic of the funk´s world, such as slang, neologisms and transgressions of the rules of standard language learned. To this end, we investigated the speech of the Funk, basing ourselves on the Discourse Analysis of the French line, using mainly Maingueneau´s studies in their new trends. The survey sample consists of about 15 lyrics of funk, of which 3 were selected for analysis and the remainder used for illustration throughout the work. In the course of the study and, especially, in the analysis, we realize that the speeches of funk lyrics to report the suburban life and the peculiar problems to that medium, which, when expressed in dances, prove to be eroticized and are mainly marked by choreography, which exhibit transgressive body of man and woman. The global semantic categories show is appropriate for the goals we set ourselves. Although we stick to the dimensions of the themes and vocabulary, this allowed us to see it as a specific social class funkeiros class devoid of prestige, but their speeches, as a ritual enunciation, exposing the harsh political reality, where socioeconomic and cultural living